The association between immune markers and recent suicide attempts in patients with serious mental illness: A pilot study. (September 2017) - Dickerson, Faith; Adamos, Maria; Katsafanas, Emily; Khushalani, Sunil; Origoni, Andrea; Savage, Christina; Schweinfurth, Lucy; Stallings, Cassie; Sweeney, Kevin; Alaedini, Armin; Uhde, Melanie; Severance, Emily; et al.
Abstract: Previous studies have identified elevations in markers of gastrointestinal inflammation in schizophrenia and mood disorders but studies have not measured the association between these markers and recent suicide attempts. We assessed 210 patients receiving treatment for schizophrenia, bipolar disorder, or major depression. We employed the Columbia Suicide Severity Rating Scale to identify recent and lifetime suicide attempts (actual, aborted, and interrupted). Psychiatric participants and a control group of 72 individuals without a psychiatric disorder had a blood sample drawn from which were measured specific markers of gastrointestinal inflammation and also C-Reactive protein (CRP). A total of 20 (10%) of psychiatric participants had a suicide attempt in the previous one month and 95 (45%) an attempt during their lifetime but not in the previous one month. The recent attempters had significantly elevated levels of antibodies to yeast mannan from Saccharomyces cerevisiae (ASCA), the food antigen gliadin, and bacterial lipopolysaccharide (LPS) compared with the non-psychiatric group when adjusting for demographic and clinical variables. These markers were not elevated in individuals with a past, but not recent, suicide attempt history. Our study indicates that there is evidence of gastrointestinal inflammation in some individuals who have had a recent suicide attempt. Highlights: This study examined markers of inflammation and suicide attempts. The recent attempters had elevated levels of antibodies to intestinal antigens. These markers were not elevated in those with only a past suicide attempt. Prospective studies are needed to determine the predictive value of these markers.